Efficacy and safety outcomes of ticagrelor compared with clopidogrel in Chinese elderly patients with acute coronary syndrome - Wang HD; Wang X (Dove Medical Press, 2016)
Huidong Wang,1 Xin Wang2 1Geriatric Department, The Fourth Clinical College of Harbin Medical University, Harbin, 2Geriatric Department, Daqing Oilfield General Hospital, Daqing, Heilongjiang, People’s Republic of China Objective: This study was designed to investigate the efficacy and safety outcomes of ticagrelor in comparison with clopidogrel on a background of aspirin in elderly Chinese patients with acute coronary syndrome (ACS).Patients and methods: A double-blinded, randomized controlled study was conducted, and 200 patients older than 65 years with the diagnosis of ACS were assigned 1:1 to take ticagrelor or clopidogrel. The course of treatment was required to continue for 12 months.Results: The median age of the whole cohort was 79 years (range: 65–93 years), and females accounted for 32.5% (65 patients). Baseline characteristics and clinical diagnosis had no significant difference between patients taking ticagrelor and clopidogrel; they were also balanced with respect to other treatments (P>0.05 for all). The risk of cardiovascular death was significantly lower in patients taking ticagrelor compared with clopidogrel, as was the risk of myocardial infarction (P<0.05 for all); there was no difference in the risk of stroke (P>0.05). Ticagrelor was more effective than clopidogrel in decreasing the primary efficacy end point (cardiovascular death, myocardial infarction, and stroke, P<0.05). The all-cause mortality was not significantly different between patients taking ticagrelor and clopidogrel (P>0.05). The difference in the risk of bleeding, platelet inhibition and patient outcomes major bleeding (life-threatening bleeding and others), and platelet inhibition and patient outcomes minor bleeding was not evident between patients taking ticagrelor and clopidogrel (P>0.05 for all).Conclusion: The current study in elderly Chinese patients with ACS demonstrated that ticagrelor reduced the primary efficacy end point at no expense of increased bleeding risk compared with clopidogrel, suggesting that ticagrelor is a suitable alternative for use in elderly Chinese patients with ACS. Keywords: acute coronary syndrome, Chinese elderly, clopidogrel, ticagrelor